Designing Key Risk Indicator Threshold and Risk Mitigation Strategies - Lina Apriliana; Vera Diyanty (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this research is to design a Key Risk Indicator (KRI) for the significant risks that have the potential to hinder the achievement of the company's targets, as well as to analyze the implementation of Law No. 4 of 2023, Article 252, regarding human resource development. The research is a case study of PT XYZ, which operates in the financing sector. The method used in this study is qualitative, with data collection through interviews and company document reviews. The KRI design is carried out by reviewing company documents, such as the risk register, to identify significant risks related to potential failures in achieving the company's targets, as reflected in the Key Performance Indicators. Then, the intermediate causes, root risks, KRI indicators, and threshold limits for these significant risks are determined. The significant risks identified include granting loans to debtors without considering their SLIK (Indonesian Credit Information System) history and delinquency, as well as analyzing the debtor's/candidate debtor's capacity without aligning with the actual conditions. The design of the KRI is expected to assist the company in monitoring events that indicate the occurrence of risks and enable early mitigation of risks that could affect performance achievement. Meanwhile, the risk mitigation design focuses on human resource development in accordance with Law No. 4 of 2023, Article 252. The risk mitigation design includes: 1) developing human resources through a refresher program by setting competency standards, 2) building a learning culture within the company, and 3) rotating Relationship Manager employees to the Collection department and removing them from Marketing activities.